Chemical kinetics in solar to chemical energy conversion: The photoelectrochemical oxygen transfer reaction - Ronald Vargas; David Carvajal; Lorean Madriz; Benjamín R. Scharifker (Energy Reports, 2020)
After introducing the basic aspects of the photoelectrochemical processes for the oxygen transfer reaction, we present the simplest kinetics models that have been built to represent the dynamics of light-induced redox reactions. Additionally, we discuss the basic chemical kinetics formalism used in photocatalysis and photoelectrochemistry, where interplay between the oxidation process and non-equilibrium adsorbed states is considered. We also comment about the experimental developments related to the treatment of wastewater with electricity or H2 generation. Finally, we discuss the need to measure reaction rates to determine and compare the physicochemical parameters describing the chemical interactions during photoelectrochemical processes, in order to understand these reactive systems and apply them to new challenges related to the environment and energy.
Keywords: 330; Photoelectrochemistry; Kinetics models; Photocatalysis; Wastewater treatment; H2 solar fuel